2014
DOI: 10.1007/s00432-014-1623-5
|View full text |Cite|
|
Sign up to set email alerts
|

Transglutaminase 2 inhibitor abrogates renal cell carcinoma in xenograft models

Abstract: TGase 2 inhibitor GK921 abrogates RCC growth in xenograft tumor models, suggesting the possibility of a new therapeutic approach to RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…PSMA represents the disease state related to RCC staging and neovascularization due to the hematogenous invasion or spread of renal tumor cells [17, 26]. TGase–2 [14, 27] and PD-L1 [25] were also recently described as ineffective prognostic markers, similar to in this study, and are related to inflammatory reactions and disease progression such as metastatic invasion or therapeutic resistance [14, 27, 28]. (Table 3)…”
Section: Discussionmentioning
confidence: 60%
“…PSMA represents the disease state related to RCC staging and neovascularization due to the hematogenous invasion or spread of renal tumor cells [17, 26]. TGase–2 [14, 27] and PD-L1 [25] were also recently described as ineffective prognostic markers, similar to in this study, and are related to inflammatory reactions and disease progression such as metastatic invasion or therapeutic resistance [14, 27, 28]. (Table 3)…”
Section: Discussionmentioning
confidence: 60%
“…In cancer, TGase 2 knock down causes down regulation of cancer progression because the roles of TGase 2 in cancer converge, promoting cancer progression by way of adhesion, proliferation, and EMT (reviewed in [44,83]). TGase 2 knock down or inhibition by single targeting specifically induces an anti-cancer effect in ccRCC through stabilization of p53, because p53 binds directly to TGase 2 and is thus chaperoned to the autophagosome for degradation [19][20][21]23,67,71]. This is only possible in ccRCC because over 90% of p53 in ccRCC is wild type.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TGase 2 knock down induced p53-mediated cell death [19] and that inhibition of TGase 2 by a single treatment of 0.2 mg/kg of streptonigrin showed almost a complete response of therapeutic effect [23] in ccRCC xenograft models. A series of reports showed that in ccRCC cell lines, cell death was induced by TGase 2 knock down using siRNA of TGase 2, while TGase 2 knock down did not lead to any cell death effect in the normal immortalized cell HEK293 [19][20][21]23,67]. This implies that ccRCC specifically employs TGase 2 for survival.…”
Section: Tgase 2 In Ccrccmentioning
confidence: 99%
See 1 more Smart Citation
“…2.3.2.13) between the γ-carboxamide groups of peptide-bound glutamine residues, which act as acyl donors, and the γ-amino groups of protein-and peptide-bound lysine residues, which act as acceptors (Folk 1983). Recently, TGase 2 has been identified as a therapeutic target (Kang et al 2016;Ku et al 2013Ku et al , 2014 as well as a significant clinicopathologic marker in human clear cell renal cell carcinoma (RCC) (Park et al 2015). RCC shows highly increased expression of TGase 2 regardless of mutations, while low expression has been detected in the normal kidney epithelial cell.…”
Section: Introductionmentioning
confidence: 99%